Pemanfaatan Lembaran Daerah sebagai Terbitan Resmi Pemerintah di Perpustakaan Kantor Gubernur Provinsi SumateraBarat - Mutia, Ezzy; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
This article discusses how to use the sheet area in Library West Sumatra Provincial Governor's Office and the constraints in the use of the sheet area in the Library Office of the Governor of West Sumatra Province. Based on the discussion concluded, namely: (1) Use of the sheet area in Library West Sumatra Governor's Office used according to the circumstances and needs of the parties concerned. In terms of utilization of the area as a reference sheet, as consideration, for comparison, as a decision maker, as a report and as research materials that are interrelated with each other in local government activities. (2) Constraints in the use of the area as a reference sheet, material considerations, comparative material, material decision makers, material reports, and research materials, ie the number of collection areas missing sheets, lack of human resources to manage the library, not a collection of neat cause difficult to obtain information, a lack of infrastructure such as rack collection, much of the data has not been compiled into a computer causes people not able to access all areas of government policy issued in one year. Keywords: regional gazette; local regulations; government issue